(untitled) (Global Journal of Science Frontier Research, 2021)
At the same time, the demand for water and energy resources around the world is growing year by year.This requires the efficient use of available water and energy resources.Currently, attention is paid to the low energy consumption of devices manufactured in all areas.In particular, in our country, scientific research is being conducted to create energyefficient devices in the water management system.This article is devoted to the positive solution of the listed problematic issues.